1974
DOI: 10.1111/j.1471-4159.1974.tb11593.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF l‐DOPA ON BRAIN CONCENTRATION OF DOPAMINE AND HOMOVANILLIC ACID IN RATS AFTER CHRONIC MANGANESE CHLORIDE ADMINISTRATION

Abstract: Rats chronically treated with a high oral load of MnCl, showed decreased concentrations of dopamine and HVA in brain. A return to normal values was observed after L-DOPA injections. This suggests a disturbance in catecholamine metabolism after chronic manganese administration possibly a t the level of L-tyrosine hydroxylase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Concentrations of Mn in the substantia nigra and caudateputamen have been associated with decreases in the striatal dopamine concentration in both the rat and the monkey (Bird et al, 1984;Bonilla and Diez-Ewald, 1974). Our results extend previous investigations (Autissier et al, 1982;Bird et al, 1984;Bonilla and Diez-Ewald, 1974;Chandra et al, 1979) in which Mn concentration in the ventral mesencephalon was associated with decreased dopamine levels in the caudate-putamen. This suggests that Mn may inhibit dopamine production or dopamine storage and/or reduce the number of neurons in the substantia nigra.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Concentrations of Mn in the substantia nigra and caudateputamen have been associated with decreases in the striatal dopamine concentration in both the rat and the monkey (Bird et al, 1984;Bonilla and Diez-Ewald, 1974). Our results extend previous investigations (Autissier et al, 1982;Bird et al, 1984;Bonilla and Diez-Ewald, 1974;Chandra et al, 1979) in which Mn concentration in the ventral mesencephalon was associated with decreased dopamine levels in the caudate-putamen. This suggests that Mn may inhibit dopamine production or dopamine storage and/or reduce the number of neurons in the substantia nigra.…”
supporting
confidence: 87%
“…(Newland and Weiss, 1992), intratracheal (Mustafa and Chandra, 1971), or inhalation routes (Bird et al, 1984). After Mn 2 > administration by any of these other routes, it took weeks to months for a decrease, if any, in the spontaneous motor activity to occur and even then only inconsistent changes in the dopamine concentration in the striatal tissue could be demonstrated (Autissier et al, 1982;Bird et al, 1984;Bonilla and Diez-Ewald, 1974;Bull, 1978;Chandra et al, 1979;Chandra and Shukla, 1981;Cotzias et al, 1974;Eriksson et al, 1987;Komura and Sakamoto, 1992;Mustafa and Chandra, 1971;Shukla and Chandra, 1979;Subhash and Padmashree, 1991).…”
mentioning
confidence: 99%
“…The cellular, intracellular and molecular mechanisms underlying the Mn-induced neurotoxicity are both doseand time-dependent [3,8], while they are also thought to be numerous and not well understood. Most mechanisms involve the Mn-induced free radical production [9] and changes in the function of nearly all systems of neurotransmission [10][11][12][13]. In view of the above, high-level short-term exposure to Mn might provide a suitable experimental basis for the evaluation of the possible primary targets of Mn neurotoxicity, and contribute to the uncovering of the mechanisms involved in the induction of the clinical neuropsychiatric manifestations.…”
mentioning
confidence: 99%
“…The clinical symptoms of this disease are similar to those of Parkinson's disease (Cotzias, 1966;Mena et al, 1967;Cotzias et al, 1971), and depletion of brain monoamines and many of the symptoms that occur in Parksinson's disease are alleviated by treatment with 3,4-dihydroxyphenylalanine (dopa) (Ehringer and Hornykiewicz, 1960;Cotzias et al, 1969). Neff et al (1969), Mustafa and Chandra (1971), and Bonilla and Diez-Ewald (1974) demonstrated significant decreases in the levels of dopamine and norepinephrine in the brains of animals exposed to manganese. However, little information was obtained regarding the metabolism of serotonin, another biologically active monoamine, in manganese poisoning.…”
Section: Introductionmentioning
confidence: 90%